Digital tools for the study of historical performing arts: the PerformArt database and thesaurus - Manuela Grillo (Umanistica Digitale, 2021)
The aim of this report is to show two main results of the ERC project PerformArt: a database and a thesaurus. Over a period of five years, the team of the project developed a very rich database; the development of a thesaurus became necessary to browse through this mass of data.